2011
DOI: 10.1371/journal.pone.0020595
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Birth Weight and Early Infant Weight Gain on Insulin Resistance and Associated Cardiovascular Risk Factors in Adolescence

Abstract: BackgroundLow birth weight followed by accelerated weight gain during early childhood has been associated with adverse metabolic and cardiovascular outcomes later in life. The aim of this study was to examine the impact of early infant weight gain on glucose metabolism and cardiovascular risk factors in adolescence and to study if the effect differed between adolescents born small for gestational age (SGA) vs. appropriate for gestational age (AGA).Methodology/Principal FindingsData from 30 SGA and 57 AGA healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
3
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(102 citation statements)
references
References 44 publications
4
93
3
2
Order By: Relevance
“…Growth restraint before birth is thought to confer such risk, particularly when followed by excessive weight gain after birth (3). By the postnatal age of 4 months, SGA infants already have an altered endocrine-metabolic profile with elevated concentrations of circulating IGF-I and high-molecular weight adiponectin (4).…”
mentioning
confidence: 99%
“…Growth restraint before birth is thought to confer such risk, particularly when followed by excessive weight gain after birth (3). By the postnatal age of 4 months, SGA infants already have an altered endocrine-metabolic profile with elevated concentrations of circulating IGF-I and high-molecular weight adiponectin (4).…”
mentioning
confidence: 99%
“…2 More recent studies have shown that the postnatal growth pattern in infancy is also an important factor in the expression of later disease. [3][4][5][6] Indeed, it is a matter of great interest to know how the interaction between pre-and postnatal growth affects the development of cardiometabolic risk factors.…”
mentioning
confidence: 99%
“…However, metabolic assessments in these studies were obtained in later childhood 4 or adolescence. 5 Contrary to these reports, Lurbe et al 2 found that weight gain within the first 6 months had no effect on metabolic variations measured at age 5 years in SGA infants. Based on a systematic review of published evidence on the association of birth weight with type 2 diabetes mellitus in adults, Whincup et al 6 reported that in most populations birth weight was inversely related to type 2 diabetes mellitus.…”
Section: See Related Article P 1326-1332mentioning
confidence: 91%
“…Subsequent studies to test this idea reported that overnutrition in early infancy was associated with later metabolic abnormalities 4,5 and suggested that overnutrition with accelerated weight gain in the first months of life contributed to adverse metabolic changes. However, metabolic assessments in these studies were obtained in later childhood 4 or adolescence.…”
Section: See Related Article P 1326-1332mentioning
confidence: 99%